Effects of delaying character instruction in a Chinese as a foreign language classroom on affective outcomes. (22nd October 2018) - Walker, Jesse; Poole, Frederick
Abstract : This study surveyed 58 sixth grade students in four different Chinese as a second language classrooms about their anxiety, self-efficacy and attitudes towards learning Chinese as a foreign language when taught using three different approaches: Pinyin only instruction (POI), character only instruction (COI) and character instruction with Pinyin located above the character (PCI). All participants completed a fivepoint Likert scale battery of 38 affective items and six open-ended questions. Our findings indicate that students in the POI condition reported significantly lower anxiety levels than participants in the COI condition. Our findings suggest that POI has potential benefits for learners in that it lowers anxiety while providing similar levels of motivation as COI and PCI.